Recent progress in shattered pellet injection technology in support of the ITER disruption mitigation system*This work was supported by the Oak Ridge National Laboratory managed by UT-Battelle, LLC for the U.S. Department of Energy under Contract No. DE-AC05-00OR22725. (2nd September 2021) - Gebhart, T.E.; Baylor, L.R.; Ericson, M.N.; Meitner, S.J.; Qualls, A.L.; Rasmussen, D.A.
Abstract: Shattered pellet injection (SPI) has been selected as the baseline technology for the disruption mitigation (DM) system for ITER. Typical SPI utilizes cryogenic cooling to desublimate low pressure (<100 mbar) gases onto a cold zone within a pipe gun barrel, forming a cylindrical pellet. Pellets are dislodged from the barrel and accelerated using either a gas driven mechanical punch or high-pressure light-gas delivered by a fast-opening valve. SPI technology developed at Oak Ridge National Laboratory is currently deployed and operational on DIII-D, JET, and KSTAR. These SPI systems are used in experiments for physics scaling to ITER thermal mitigation and runaway electron dissipation/avoidance. The pellet sizes used for these machines are in the range of 4 to 12.5 mm in diameter with length to diameter ratios ( L / D ) of ∼1.5. The current plan for ITER SPI is to utilize pellets that are 28.5 mm in diameter with an L / D of ∼2. The large pellet sizes, high steady-state magnetic fields, and limitations of operating in a radiation environment render much of the current technology unusable. In addition to technology improvements, a deeper understanding of pellet material properties, formation, and release is being developed for implementation in future SPI designs, specifically ITER.